Changes in schizogony and drug response in two lines of rodent Plasmodium, P. berghei NK 65 and P. berghei ANKA - Biarnais T.; Landau I.; Richard-Lenoble D. (Parasite, 2002)
White mice were infected with two strains, ANKA and NK 65, of Plasmodium berghei. The parasites were subjected to chloroquine pressure (60 mg/kg at each passage) during 20 passages. We then compared the behaviour of the strains as they acquired chemoresistance. The drug resistance was estimated by the 2 % delay time test (D2%), and the schizogonic rhythm by the synchronicity index (SI). Before drug pressure, the ANKA strain had a D2% of 4.34, and a SI of 0.2. This strain became highly drug resistant, but synchronicity increased: the D2% was 2.93, and the SI was 0.36 at the 20th passage. The NK 65 strain had an initial D2% of 4.1 2, and an SI of 0.2. The chemoresistance acquired during 20 passages was very irregular for this strain: after drug pressure, the D2% was 2.03 and the SI was 0.28. Drug pressure was then removed (for both strains), for 10 passages (no chloroquine). Resistance and synchronicity returned to their initial values. The two strains behaved very differently, in terms of their affinity for reticulocytes, and with chloroquine activity which favours an increase in SI because only merozoites are preserved.